2008
DOI: 10.1007/s10562-008-9400-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-programmed Studies of Coke Resistant Ni Catalyst for Carbon Dioxide Reforming of Methane

Abstract: Argon glow discharge plasma was applied for drying the impregnated Ni/SiO 2 catalyst instead of the drying thermally. Such plasma treated catalyst significantly inhibits the coke formation from methane decomposition.The methane-derived carbon shows an improved reactivity against CO 2 . This can result in a better balance of coke formation and gasification by CO 2 when the plasma-treated Ni/SiO 2 catalyst is used for the CO 2 reforming of methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Most often, catalyst are synthesized using (wet/dry) impregnation or (co‐)precipitation which combines several unit operations. It can be useful to add plasma treatment to the standard process to enhance several catalyst properties such as the dispersion and the particle sizes,11, 69–73 but a more interesting approach exists in the replacement of the reduction or calcination step by a plasma treatment 74–80…”
Section: Catalyst Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Most often, catalyst are synthesized using (wet/dry) impregnation or (co‐)precipitation which combines several unit operations. It can be useful to add plasma treatment to the standard process to enhance several catalyst properties such as the dispersion and the particle sizes,11, 69–73 but a more interesting approach exists in the replacement of the reduction or calcination step by a plasma treatment 74–80…”
Section: Catalyst Treatmentmentioning
confidence: 99%
“…Several authors have reported the addition of a plasma treatment step to the catalyst's synthesis procedure. The treatment is most commonly applied before the conventional calcination and is often found to enhance catalytic properties 11, 69–73, 81–86. Several advantages can be obtained by this approach: smaller particle sizes, increased dispersion, and increased activity.…”
Section: Catalyst Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel catalyst preparation has become a hot topic and, in some cases, a challenge to chemists worldwide. Recently, using various plasmas for catalyst preparation has attracted a lot of attentions [2][3][4][5][6][7][8][9][10]. Plasma is a substance in which part of the atoms or molecules are effectively ionized.…”
Section: Introductionmentioning
confidence: 99%
“…The major progresses have been summarized in the previous review article [12]. The recent researches confirmed that plasmas can be efficiently and effectively applied for the size and shape control of metal or metal oxide nano-particles for catalytic uses [3,4,7]. Especially, argon or air plasma can be directly applied for the reduction of noble metal ions at room temperature [13].…”
Section: Introductionmentioning
confidence: 99%